Erythema multiforme in time of COVID-19. - Mazzotta, F.; Troccoli, T. (European Journal of Pediatric Dermatology, 2020)
Erythema multiforme is a skin reaction to numerous factors, the best known of which is Herpes simplex virus. The child of the current report in full SARS-CoV-2 pandemic presented after flu symptoms characteristic vasculitic lesions of the feet and after a few days erythema multiforme. The authors of the current report suggest a probable relationship of these symptoms with COVID-19.